A novel sensor for measuring the inner pressure of catheters for clinical use - Accoto, Dino (2019)
In numerous clinical procedures requiring the infusion of a fluid (gas or liquid) it is necessary to monitor the infusion pressure. To this purpose, several devices have been developed so far. Such devices are generally disposable, with a pressure transducer in direct contact with the infusion fluid. In this paper, we describe the design and development of a dry infusion pressure measurement system, sensing the pressure-induced radial displacement of the external surface of polymeric catheters. Such displacement is first amplified using a near-to-singularity elastic beam and then transduced using a Hall effect displacement sensor. We start describing the working principle of the whole system, then we detail the design process. Finally, we present the static calibration on two widely used biomedical catheters.